EFFECTS OF VARYING CONCENTRATIONS OF THE CRUDE AQUEOUS AND ETHANOLIC - Adenusi, Adedotun Adesegun; Odaibo, Alexander Bababunmi (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
This study evaluated, using replicated laboratory bioassays, the toxicities of the crude aqueous andethanolic extracts of Dalbergia sissoo Roxb. 1832 (family Leguminosae) fruits, leaves, roots and stem barkagainst egg masses of Biomphalaria pfeifferi (Krauss, 1848), the snail intermediate host of Schistosoma mansoni(Sambon, 1907) in Nigeria. Viable 0-24 hr-old embryonated egg masses were separately exposed to fivedifferent concentrations (7.81-2000 mg/l) of extracts for 24 hrs, washed in dechlorinated tap water and incubatedat room temperature for a maximum of 4 weeks. The LC50 and LC90 values of test extracts for egg masses werecalculated by probit analysis. The activities of the tested extracts were concentration-dependent. However, onlythe ethanolic extract of the fruits demonstrated significant activity (24 hr-LC90 value < 100 mg/l: 89.29 mg/l).Mortalities of eggs were manifested at the gastrula/exogastrula and or the prehatch snail stage of development.The percentage of dead embryos at the prehatch snail stage decreased while the deaths of embryos at thegastrula/exogastrula stage increased, with increasing concentration of extract. Lethality of the ethanolic extractof D. sissoo fruits to embryonated egg masses of B. pfeifferi is an added advantage to its potential developmentfor use as a plant molluscicide, as the overall efficacy of a molluscicide is greatly enhanced if it also showssignificant toxicity towards snail eggs.